Promosi Kesehatan Tentang HIV/AIDS Melalui Penyuluhan Kesehatan di SMK Mitra Maritim Indramayu - Nengsih Yulianingsih; Priyanto Priyanto; Sally Yustinawati Suryatna; Niken Wulan Hasthi Murti (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Health Promotion on HIV/AIDS is very important for adolescents to improve their understanding of transmission, prevention, treatment, and its social impacts. The Community Service Program (PKM) by the Indramayu State Polytechnic was implemented at SMK MITRA MARITIM INDRAMAYU, Indramayu Regency, with the aim of improving students' understanding of HIV/AIDS. The activity methods include material presentation, interactive discussions. A total of 45 students participated in this program. Evaluation was carried out through pre-tests and post-tests to measure the effectiveness of education. The results showed a significant increase in students' understanding of HIV/AIDS, including the differences between HIV and AIDS, symptoms, and the importance of antiretroviral therapy (ARV). In addition, students became more aware of the social stigma against People with HIV/AIDS and how to provide support to friends who are infected. This program not only strengthens awareness of HIV/AIDS, but also empowers students to become agents of change. It is hoped that this program can be sustainable in order to form a younger generation that is more health conscious.